2014
DOI: 10.4028/www.scientific.net/amm.662.225
|View full text |Cite
|
Sign up to set email alerts
|

Applied Technology in Diaper-Based UTI Testing for Elder People by Using Nitrite Ion Selective Electrode

Abstract: Urinary tract infections (UTI) are common infection diseases in the hospitals, especially for the elder people. Detecting UTI for the elder people is difficult and time-consuming procedure. Since measuring nitrite directly in urine is often employed in the diagnosis of UTI, a nitrite ion selective electrode (ISE) was investigated in this study in order to detect UTI samples directly on used diapers of patients. With a commercial ISE sensor for nitrite, the detecting system was built to quickly and precisely qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Biosensors have broad applications in drug discovery, medical diagnostics [1,2], environmental monitoring and food safety [3]. The concentration of specific analytes and their reaction kinetics can be identified in biosensors [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Biosensors have broad applications in drug discovery, medical diagnostics [1,2], environmental monitoring and food safety [3]. The concentration of specific analytes and their reaction kinetics can be identified in biosensors [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic devices are powerful tools for analytical chemistry, biology, diagnostics, and biomedical research. Several microfluidic devices have been developed to detect adenosine triphosphate (ATP) [1,2], nitrite [3], and bacteria [4] for Urinary tract infection detection [5]. Microfluidic devices can be miniaturized and integrated, thereby affording advantages such as easy handling, portability, and short operating time, low cost, reduced consumption of sample and reagents, and high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, current thinking is that it is considered crucial to keep elder patients healthy by matching or realizing "Diaper zero" program as developed in Japan (Liao et al, 2015) where they are concerned about the dignity of patients although diapers are frequently used as an absorbent product in the geriatric setting (Becher et al, 2013). Feng and Dong (2014) and Hui et al (2014) reported on ways to improve complications of diaper usage and monitor the incontinence conditions of frail elderly. However diaper usage is a cause of frequent urinary tract infection (UTI) for the elder patients (Feng and Dong, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Feng and Dong (2014) and Hui et al (2014) reported on ways to improve complications of diaper usage and monitor the incontinence conditions of frail elderly. However diaper usage is a cause of frequent urinary tract infection (UTI) for the elder patients (Feng and Dong, 2014). Gibbs (2014) warned that adults requiring diapers are at increased risk of creating an environment of heat and moisture, which predisposes skin to damage.…”
Section: Introductionmentioning
confidence: 99%